2014
DOI: 10.3171/2014.2.jns131423
|View full text |Cite
|
Sign up to set email alerts
|

Hoarding symptoms and prediction of poor response to limbic system surgery for treatment-refractory obsessive-compulsive disorder

Abstract: Object Recent findings have suggested a correlation between obsessive-compulsive disorder (OCD) symptom dimensions and clinical outcome after limbic system surgery for treatment-refractory patients. Based on previous evidence that the hoarding dimension is associated with worse outcome in conventional treatments, and may have a neural substrate distinct from OCD, the authors examined a large sample of patients undergoing limbic surgery (40 with capsulotomy, 37 with cingulotomy) and investigated if symptom dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 54 publications
(58 reference statements)
2
10
0
Order By: Relevance
“…In agreement with these findings, prior studies of compulsive hoarders have demonstrated poorer treatment outcomes to a variety of treatment approaches including CBT (Abramowitz et al, 2003b; Rufer et al, 2006), behavioral therapy (Mataix-Cols et al, 2002), pharmacologic (Mataix-Cols et al, 1999), intensive multimodal treatment in the context of a partial hospitalization program (Saxena et al, 2002), and limbic surgery (Gentil et al, 2014). Taken together, these findings support the recent view of compulsive hoarding as a distinct disorder separate from OCD that may require different treatment approaches (Pertusa et al, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…In agreement with these findings, prior studies of compulsive hoarders have demonstrated poorer treatment outcomes to a variety of treatment approaches including CBT (Abramowitz et al, 2003b; Rufer et al, 2006), behavioral therapy (Mataix-Cols et al, 2002), pharmacologic (Mataix-Cols et al, 1999), intensive multimodal treatment in the context of a partial hospitalization program (Saxena et al, 2002), and limbic surgery (Gentil et al, 2014). Taken together, these findings support the recent view of compulsive hoarding as a distinct disorder separate from OCD that may require different treatment approaches (Pertusa et al, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…Compulsive hoarding is characterized by collecting, and difficulty discarding, large quantities of seemingly useless objects, such that living spaces are cluttered and considerable distress and/or impairment are experienced [4]. Among OCD cases, those with hoarding often have a more severe illness, poorer response to treatment, co-occurring mood, anxiety, and other Axis I disorders, and schizotypal, avoidant, dependent, and obsessive-compulsive personality traits [5-11]. In addition, neurocognitive and neuroimaging studies have found differences in executive functioning, and level of activation in specific brain regions, between OCD cases with and without hoarding [12-17].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Gentil et al (2014) found hoarding symptom to be a predictor of poor response to neurosurgical intervention in OCD [86]. …”
Section: Discussionmentioning
confidence: 99%